An Instrument Anomaly in the Mars Exploration Rover Pancam 1, 009‐nm Filter (R7): Characterization, Simulation, Correction, and Preliminary Verification. Issue 1 (25th January 2019) - Jakobsen, Simone J.; Kinch, Kjartan M.; Madsen, Morten Bo; Bell, James F.; Wellington, Danika; Dajose, Lorinda; Alizai, Khaled
Abstract : During pre‐flight calibration of the panoramic camera (Pancam) instrument on board the Mars Exploration Rovers MER A (Spirit) and MER B (Opportunity), a discrepancy was noted between 11‐band spectra extracted from Pancam images of the camera's radiometric calibration target and reflectance spectra obtained with a spectrometer. This discrepancy was observed in the longest‐wavelength filter of the camera (the longpass R7 filter with system λeff  = 1, 009 nm) and consisted of a reduction in contrast between bright and dark regions. Here we describe and characterize this effect. We propose that the effect arises because long‐wavelength photons close to the silicon band‐gap at 1, 100 nm are allowed through the R7 filter, pass through the bulk charge‐coupled device, scatter from the backside, pass through the charge‐coupled device again, and are registered in a pixel other than the pixel through which they originally entered. Based on this hypothesis we develop a model capable of accurately simulating the effect, and correct for it. We present preliminary results from testing this correction on preflight, as well as in‐flight, images. The effect is small, but in some specific cases in small regions of high contrast, the effect is significant. In in‐flight images of Martian terrain we observed the signal in dark shadows to be artificially inflated by up to ∼ 33% and analysis of early‐mission calibration target images indicated that the reduced contrast due to the artifact is equivalent to >100 DN (full well = 4095 DN) for a hypothetical perfectly dark pixel. Key Points: An anomalous effect of the Pancam 1, 009‐nm filter has been successfully modeled and simulated based on a hypothesis for the physical origin A correction to the effect has been developed, based on the model, which successfully removes it, without adding any artificial signal The correction has been verified using independent, in‐flight R7 images of the Martian surface, and of the calibration target